Synthesis and x-ray structure of a cluster complex with facial coordination of cyclooctatetraene to a Co2Ni triangle - Wadepohl, Hubert; Gebert, Stefan; Merkel, Rüdiger; Pritzkow, Hans (Chemical communications, 1999)
The reaction between [(η-C5H5)NiCo3(CO)9] and cyclooctatetraene yields [Co2Ni(CO)6(µ3-η2:η3:η3-C8H8)] with a cyclooctatetraene ligand in the facial coordination mode to a heterometallic Co2Ni triangle.
Gesehen am 25.01.2019
Im Titel ist die Zahl "2" tiefgestellt